1952
DOI: 10.1302/0301-620x.34b4.608
|View full text |Cite
|
Sign up to set email alerts
|

Acute Haematogenous Osteitis in Childhood

Abstract: Before effective chemotherapy} Aetiological factors Bacteriology Bones affected Clinical course Radiographic changes Mortality Autopsy findings Complicati ons Contemporary methods of treatment End results GROUP n (1 9 4 1-1 9 4 5) (Sulphathiazole era} Aetiological factors Bacteriology Bones affected Clinical course Radiographic changes Mortality Autopsy findings Complications Contemporary methods of treatment End results GROUP III (I945-1 9 4 9 } (Penicillin era) Aetiological factors Bacteriology Bones affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

1961
1961
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…In general our results compare favourably with those of others who have been treating acute osteomyelitis by medullary decompression (White and Dennison, 1952;Trueta and Morgan, 1954).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In general our results compare favourably with those of others who have been treating acute osteomyelitis by medullary decompression (White and Dennison, 1952;Trueta and Morgan, 1954).…”
Section: Resultssupporting
confidence: 83%
“…Our cases have recently been reviewed by one of us (Shandling, 1960), and our findings in regard to age and sex incidence, social status, pre-existing septic foci and predisposing trauma are in keeping with those of others (Altemeier and Helmsworth, 1945;Agerholm and Trueta, 1946;Caldwell and Wickstrom, 1950;White and Dennison, 1952;Dennison, 1952;Trueta and Morgan, 1954). The bones most commonly affected were upper tibiae, lower femora and tibiae and upper femoral shafts (Fig.…”
supporting
confidence: 72%
“…An early study of the treatment of paediatric osteomyelitis with penicillin reported resistance rates of only 2.4%. 2 Over the next 50 years these rose rapidly to 60% to 80%, and since 1999 the rates for MRSA are addressed specifically. They vary enormously, depending largely on geographical location, from 0% in Saudi Arabia 40 to 71.4% in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Delay in diagnosis and inappropriate treatment can result in sepsis, chronic infection, disruption of longitudinal bone growth and angular deformity. 2,3 Correct and timely treatment improves outcome; however, with evolving microbiology, including the emergence of methicillin-resistant Staphylococcus aureus (MRSA), early selection of the correct antibiotic is vital.…”
mentioning
confidence: 99%
“…In addition, we assessed and compared the pathogens responsible, the routes and duration of antibiotic therapy, the need for surgery and the complications encountered with those of earlier series. [1][2][3][4][5][6][7][8][9][10] The study repeated that of Craigen, Watters and Hackett 11 on the same reference population between 1970 and 1990. By using identical methods we were able to observe trends, particularly with regard to incidence, over a period of 28 years.…”
mentioning
confidence: 75%